2018
DOI: 10.32422/mv.1584
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary scholarship schemes as institutionalised migration of highly skilled labou

Abstract: Providing scholarships has become an integral part of the global higher education and so has research on its impacts. This article examines the tertiary scholarship scheme of the Czech government for providing scholarships to students from the global South as a part of its development cooperation programme with a double goal. Firstly, it examines the programme's development effectiveness from the perspective of migration studies, and secondly, it investigates the underlying motivation factors which influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These studies usually overlook university experience satisfaction as a possible influencing factor. Some include academic satisfaction either as a variable on its own (Trice & Yoo, 2007), or satisfaction with university experience is treated as part of social adjustment factors (Hejkrlík et al, 2018) or of academic achievement (Li & Sun, 2019). To address a lack of an agreed upon definition, this study suggests that university experiences can be understood as students' encounters with actors and services affiliated with their academic institution.…”
Section: Hypotheses Satisfaction With the University Experiencementioning
confidence: 99%
“…These studies usually overlook university experience satisfaction as a possible influencing factor. Some include academic satisfaction either as a variable on its own (Trice & Yoo, 2007), or satisfaction with university experience is treated as part of social adjustment factors (Hejkrlík et al, 2018) or of academic achievement (Li & Sun, 2019). To address a lack of an agreed upon definition, this study suggests that university experiences can be understood as students' encounters with actors and services affiliated with their academic institution.…”
Section: Hypotheses Satisfaction With the University Experiencementioning
confidence: 99%
“…The return rate identified in our survey among the alumni respondents on average 2.85 years after the end of their study was only 31%. This is lower than estimates reported in previous studies (Hejkrlík et al, 2018; Jelínek, Dessieová, & Náprstek, 2004) and far behind the return rates reported for the scholarship programmes funded from Australian or British development aid (Abimbola et al, 2016; Commonwealth Scholarships, 2017; Marsh et al, 2016) and many other development‐oriented international scholarships financed by governments of sending countries (Perna et al, 2014). Together with the relatively low intention to return, the low return rate uncovered in this study cast doubts on the Czech scholarship programme's effectiveness if conceived as a development intervention seeking to expand human capital in developing countries.…”
Section: Discussionmentioning
confidence: 59%
“…We were mainly concerned with the ques- The return rate identified in our survey among the alumni respondents on average 2.85 years after the end of their study was only 31%. This is lower than estimates reported in previous studies (Hejkrlík et al, 2018;Jelínek, Dessieová, & Náprstek, 2004) and far behind the return rates reported for the scholarship programmes funded from Australian or British development aid (Abimbola et al, 2016;Commonwealth Scholarships, 2017;Marsh et al, 2016) and many other development-oriented international scholarships financed by governments of sending countries (Perna et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation